Gut Microbiota: A Promising Milestone in Enhancing the Efficacy of PD1/PD-L1 Blockade Therapy - Zhou, Yuqing; Liu, Zhaoxia; Chen, Tingtao (Frontiers in Oncology, 2022)
In the past few decades, immunotherapy has emerged as one of the most promising strategies among current treatments of cancer. In particular, the field of PD1/PD-L1 inhibitors has been boosted, widely applied into clinical practice with potent therapeutic efficacy and remarkable survival benefits on various cancers such as melanoma, non-small cell lung cancer (NSCLC), and urothelial carcinoma (UC). However, the application of PD1/PD-L1 blockade therapy is still quite limited because of unexpected toxicities, limited response rate, and associated resistance. In consequence, searching for potential strategies that possibly resolve the existing limitations and enhance the therapeutic responsiveness of PD1/PD-L1 blockade is of great significance. Fortunately, the gut microbiome has been demonstrated to serve as a pivotal regulator in anti-PD1/PD-L1 therapy, providing a potential tool to improve anti-PD1/PD-L1 clinical efficacy. In this review, we summarized published advancements about how microbiota modulate in anti-PD1/PD-L1 therapy and illustrated its possible mechanisms, providing insights into putative manipulation of gut microbiota to elevate anti-PD1/PD-L1 effectiveness.